The Interior Design Reference + Specification Book : Everything interior designers need to know every day - Grimley, Chris, ....-; Love, Mimi, ....- (Beverly : Rockport Publishers, 2018)
Newly updated and revised, The Interior Design Reference and Specification Book is an essential sourcebook for designers, students of design, and anyone undertaking an interior design project. This comprehensive reference puts the information vital to designers - on site or in the office- at your fingertips. Detailed charts, specifications, diagrams, and ditigtal information for planning and executing projects of every scale are provided in a format that is easy to use and small enough to carry everywhere.